Comparative study between programming systems for incremental sheet forming process - Moayedfar, Majid; Abdul Rani, Ahmad Majdi; Salehi, Pouria; Tad, Varaha Venkata Lakshmi Narasimha Rao (EDP Sciences, 2014)
Incremental Sheet Forming (ISF) is a method developed to form a desired surface feature on sheet metals in batch production series. Due to a lack of dedicated programming system to execute, control and monitor the whole ISF, researchers tried to utilize programming systems designed for chip making process to suits for ISF. In this work, experiments were conducted to find suitability and quality of ISF parts produced by using manual CNC part programming. Therefore, ISF was carried out on stainless steel sheets using Computer Numerical Control (CNC) milling machines. Prior to running the experiments, a ball-point shaped tool made of bronze alloy was fabricated due to its superior ability to reduce the amount of friction and improve the surface quality of the stainless steel sheet metal. The experiments also employed the method of forming in negative direction with a blank mould and the tool which helped to shape the desired part quickly. The programming was generated using the MasterCAM software for the CNC milling machine and edited before transferring to the machine. However, the programming for the machine was written manually to show the differences of output date between software programming and manual programming. From the results, best method of programming was found and minimum amount of contact area between tool and sheet metal achieved.